DIGITAL AGRICULTURE: ANALYSIS OF VIBRATION TRANSMISSION FROM SEAT TO BACK OF TRACTOR DRIVERS UNDER MULTI-DIRECTIONAL VIBRATION CONDITIONS - Singh, Amandeep; Nawayseh, Naser; Dhabi, Yash Kumar; Samuel, Siby; Singh, Harwinder (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
The present research examines the impact of vibrations on seat-to-back transmissibility in tractor drivers. This study utilized a smart device for real-time data transmission to improve the experimentation by eliminating potential sources of error. Data was assessed using metrics such as weighted acceleration, daily exposure, power spectral density, and seat-to-back transmissibility. The seat pan and backrest were found to have high vibration levels on the vertical axis. Daily exposure response exceeded the exposure action limit of 0.5 m/s2, as specified in Directive 2002/44/EU. Power spectral densities at the seat pan and the backrest revealed dominant frequencies in the low-frequency range. Seat-to-back transmissibility demonstrated primary and secondary resonance within the 4.1-7.2 Hz and 8.2-11.8 Hz frequency ranges. Tractor manufacturers and designers could utilize the findings of this study to decrease the excessive vibration intensities and crucial resonating frequencies and thus enhance the operator’s ride comfort.